2004
DOI: 10.1046/j.1365-2893.2003.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the accuracy of long‐term prognostic estimates in hepatitis C virus infection

Abstract: Obtaining unbiased estimates of HCV prognosis is difficult because of potential biases associated with study design and calculation methods. We propose a new method for estimating fibrosis progression rates. A Markov model with fibrosis health states (F0-F4) was created. The maximum likelihood method was used to estimate stage-specific progression rates. We compared the standard method to the new method using two well-known cohort studies. The known stage distribution at the end of follow-up was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 22 publications
(34 reference statements)
2
33
0
Order By: Relevance
“…We did not have enough data to estimate stage specific progression rates. Previous studies indicate that fibrosis progression rates increase with advanced fibrosis stage [30,34]. However, a more recent study of coinfected patients found no evidence of increasing progression rates, suggesting that assuming constant progression rates may not result in biased estimates [31].…”
Section: Discussionmentioning
confidence: 95%
“…We did not have enough data to estimate stage specific progression rates. Previous studies indicate that fibrosis progression rates increase with advanced fibrosis stage [30,34]. However, a more recent study of coinfected patients found no evidence of increasing progression rates, suggesting that assuming constant progression rates may not result in biased estimates [31].…”
Section: Discussionmentioning
confidence: 95%
“…Multistage Markov models have not been widely used in hepatitis C disease progression, despite the categorical nature of biopsy assessment. Deuffic-Burban et al [15] illustrated the potential of using a Markov model to estimate hepatitis C progression rates, and Yi et al [16] showed the advantages of such an approach over routinely used methods. The model presented here allows only forward transitions, and includes adjustment for age at biopsy, gender, and PNALT status to provide estimates of cirrhosis development in a variety of subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, representation of HCV progression as a series of disease stages through a multistage model formulation has been suggested as an alternative [15,16], when transition between specific disease stages is of interest and when, crucially, only information on stage occupation (rather than stage entrance) is available. Multistage modeling is particularly appropriate to the study of fibrosis in HCV where the only information available is the stage of disease identified at biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…The FPR was approximated using one of three methods depending on the amount of data included in the report. In general, a modified version of the indirect or direct method for estimating a stage-constant FPR, appropriate for single-biopsy or serial-biopsy data (Yi, Wang, & Krahn, 2004; Thein et al 2008), respectively, was applied when the report provided the distribution of fibrosis stages.…”
Section: Methodsmentioning
confidence: 99%